2020
DOI: 10.1136/jitc-2020-001038
|View full text |Cite
|
Sign up to set email alerts
|

Synergizing sunitinib and radiofrequency ablation to treat hepatocellular cancer by triggering the antitumor immune response

Abstract: BackgroundMinimally invasive radiofrequency ablation (RFA) is used as a first-line treatment option for hepatocellular cancer (HCC) with the weaknesses of incomplete ablation, tumor recurrence, and inferior outcomes. To overcome this limitation, we proposed to develop sunitinib-RFA integrated therapy with a potential of activating anti-HCC immune response.MethodsUsing our unique murine model, we developed a novel RFA platform with a modified human cardiac RF generator. Therapeutic efficacy of sunitinib–RFA com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 36 publications
(64 reference statements)
2
61
0
Order By: Relevance
“…It was reported that RFA not only destroyed local tumor tissues but also induced antitumor immunity. 10 , 35 Consistently, our results show that RFA significantly increased the infiltration of immune cells including macrophages, DCs and NK cells in non-ablated tumor tissues, and this became more obvious after RFA + MLT treatment. NK cells showed spontaneous cytotoxic activity against tumor cells and released cytokines, which modulate the function of other immune cells, and thus played a key role in tumor immunotherapy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It was reported that RFA not only destroyed local tumor tissues but also induced antitumor immunity. 10 , 35 Consistently, our results show that RFA significantly increased the infiltration of immune cells including macrophages, DCs and NK cells in non-ablated tumor tissues, and this became more obvious after RFA + MLT treatment. NK cells showed spontaneous cytotoxic activity against tumor cells and released cytokines, which modulate the function of other immune cells, and thus played a key role in tumor immunotherapy.…”
Section: Discussionsupporting
confidence: 84%
“… 9 Although RFA could induce antitumor immunity, it is still accompanied by high recurrence rates in the treatment of early lung cancer with multiple GGNs. 10 Recently, combinations of local treatments with systemic therapy, such as targeted therapy, chemotherapy, and immunotherapy, have been suggested for reducing lung cancer recurrence and malignancy. 11 – 13 However, these treatments have significant side effects or need proper diagnosis, which makes systemic therapies unsuitable for treating early lung cancer with GGNs.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of VEGF by sunitinib also promoted DC activation and inhibited tumor angiogenesis. Combination therapy ultimately led to a remarkable increase in CD8 + T lymphocytes and DCs as well as a decrease in Tregs, thus overcoming the drawbacks of monotherapy 123 . In addition, HIFU, as a new minimally invasive ablation therapy, has become a hotspot of cancer treatment.…”
Section: Therapeutic Approaches To Promote T-cell Primingmentioning
confidence: 99%
“…The isolation of liver-infiltrating leukocytes has been described in our previous publication [60]. Briefly, liver perfusion was first performed in mice under anesthesia via the portal vein with 0.05% collagenase (Gibco, Gaithersburg, MD, USA) in Ca 2+ -free PBS at a pump speed of 4 mL/min.…”
Section: Isolation Of Liver-infiltrating Leukocytes and Spleen Lymphocytesmentioning
confidence: 99%
“…Ex vivo staining of lymphocytes with fluorochrome-labeled antibodies was performed on single-cell suspensions as described [60]. For intracellular staining, the cells were fixed and permeabilized with buffer (ThermoFisher Scientific, Waltham, MA, USA), and stained with fluorochrome-conjugated antibodies.…”
Section: Flow Cytometrymentioning
confidence: 99%